Politik Hukum Poligami (Studi terhadap Peraturan Perundang-Undangan di Negara-Negara Muslim) - Marzuki, Ismail (Fakultas Syariah IAIN Purwokerto, 2019)
This article discusses Islamic family law politics about regulating polygamy in Muslim countries. The policy of Islamic law in Muslim countries in the modern era can be categorized into two, namely uncodified law, and codified law. The Muslim countries discussed in this article are Muslim countries whose legal politics fall into the codified law category, namely: Turkey, Tunisia, Iran, Indonesia, Egypt, Morocco, and Afghanistan. Although according to fiqh polygamy is something permissible, in practice each Islamic country has a different legal policy related to polygamy, namely: (1) some countries allow polygamy, (2) some allow polygamy with strict conditions, and (3) some prohibit polygamy. In addition, this article also discusses the